The Influence of Health Education on Knowledge of Antenatal Care in Pregnant Women in Rural Areas - Utomo, Nico Krisna Prio; Gafur, Mohammat; Ma’rifah, Nunik Nurhidayatul; Putri, Dwiki Ratna; Hidayat, Cahya Tribagus; Asih, Susi Wahyuning (Al-Hijrah Indonesia, 2024)
Background: Maternal health problems are closely related to pregnant women, which contribute a lot to the current maternal mortality rate, maternal mortality can be prevented if pregnant women get good quality antenatal care services. Lack of knowledge of pregnant women about antenatal care results in a lack of care for pregnant women about their own health and the baby in their womb. One of the efforts that can be done is by conducting antenatal care so that it can monitor pregnancy and ensure the health of the mother and fetus. Objective: This study aims to analyze the effect of health education on knowledge of antenatal care for pregnant women in Karangpring Village, Jember Regency. Methods: This type of research is a quasi-experimental design with the one group pre and post-test design. This study was conducted on pregnant women as many as 17 respondents. Results: Shows the value of knowledge before being given health education in the less category of 10 people (58.8%) and the sufficient category of 5 people (29.4%) and after being given health education knowledge in the sufficient category 10 people (58.8%) and good category amounted to 7 people (41.2%). The results of the paired t-test statistic obtained a significant value less than 0.05 (p = 0.000 <0.05). Conclusion: There is an effect of health education on knowledge of antenatal care for pregnant women in Karangpring Village, Jember Regency.